2011
DOI: 10.1007/s10841-011-9437-0
|View full text |Cite
|
Sign up to set email alerts
|

Successful overwintering of arthropods in roadside verges

Abstract: In densely populated areas, roadside verges often provide the last semi-natural habitats available. Their ecological value is often stressed by bio survey results. Yet insect summer surveys potentially misjudge the value of a biotope (roadside or otherwise) since the occurrences of species may only be seasonal, or even transient. To effectively ascertain the importance of a site for insects, species must be shown to complete their life cycle there or at least be shown to successfully accomplish critical life s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 36 publications
(35 reference statements)
0
14
0
Order By: Relevance
“…The importance of certain road and railroad verges as habitat refuges for rare or declining species has been reported from previous research and conservation case studies, both in Sweden (Persson 1995, Weidow 2008, Stenmark 2010, Lennartsson 2010) and other countries (the Netherlands: Vermeulen 1993, Eversham and Telfer 1994, Van Rossum et al 2004, Schaffers et al 2012; Belgium: Tanghe and Godefroid 2000; Great Britain: Thomas et al 2002;Finland: Koivula et al 2005; South Africa: Table 1. Priority species for Swedish conservation (=red-listed species with species-wise action plans) with at least 20% of the observations nationally in road habitats.…”
Section: Discussionmentioning
confidence: 64%
“…The importance of certain road and railroad verges as habitat refuges for rare or declining species has been reported from previous research and conservation case studies, both in Sweden (Persson 1995, Weidow 2008, Stenmark 2010, Lennartsson 2010) and other countries (the Netherlands: Vermeulen 1993, Eversham and Telfer 1994, Van Rossum et al 2004, Schaffers et al 2012; Belgium: Tanghe and Godefroid 2000; Great Britain: Thomas et al 2002;Finland: Koivula et al 2005; South Africa: Table 1. Priority species for Swedish conservation (=red-listed species with species-wise action plans) with at least 20% of the observations nationally in road habitats.…”
Section: Discussionmentioning
confidence: 64%
“…, Schaffers et al. ) and may act as a source for re‐colonization of surrounding patches following disturbance (Clough et al. , Brunke et al.…”
Section: Discussionmentioning
confidence: 99%
“…Urban prairies also supported a greater abundance of brachypterous beetles, which are generally considered poor dispersers (Den Boer 1970). This suggests that urban prairies may provide these beetles, and potentially other arthropods, with overwintering and breeding habitat (Thomas et al 1992, Eversham and Telfer 1994, Noordijk et al 2011, Schaffers et al 2012 and may act as a source for recolonization of surrounding patches following disturbance (Clough et al 2007, Brunke et al 2014). An affinity toward patches with reduced disturbance intensity has been recorded for other brachypterous (Venn 2007, Gobbi and Fontaneto 2008, Pedley and Dolman 2014, hygrophilous (Magura et al 2013), and habitat-specialist groups (Halme and Niemela 1993, Deichsel 2006, Magura et al 2008, 2010b across urban gradients.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the grassland component of forest-steppes has higher species richness of spiders than pastures, and we found differences in species composition of the two habitat types for all taxa based on the multivariate analyses. The role of road verges in maintaining arthropod biodiversity within intensively managed landscape is increasingly recognised (Schaffers et al 2012;Reck and van der Ree 2015), as they may serve as linear habitats and dispersal corridors for weak-flying insects (Vermeulen 1994) and overwintering habitat for several specialists (Schaffers et al 2012;Gallé et al 2018a). In native forests, however, road verges may have a negative impact on the biota, fragmenting forest habitats by exerting barrier effects on the forest specialist species (Yamada et al 2010).…”
Section: Discussionmentioning
confidence: 99%